Influence of servant leadership on the life satisfaction of basic education teachers: the mediating role of satisfaction with job resources - Quinteros-Durand, Ronald; Almanza-Cabe, Robinson B.; Morales-García, Wilter C.; Mamani-Benito, Oscar; Sairitupa-Sanchez, Liset Z.; Puño-Quispe, Lucy; Saintila, Jacksaint; Saavedra-Sandoval, Renán; Paredes, Alcides Flores; Ramírez-Coronel, Andrés Alexis (Frontiers in Psychology, 2023)
Background: Life satisfaction is essential for teachers’ work performance and student learning. Additionally, servant leadership has been shown to be one of the best leadership practices as it promotes employee well-being and satisfaction. Moreover, satisfaction with job resources acts as a mediator in the relationship between servant leadership and life satisfaction by influencing individual and collective performance in the organization. Objective: This research aimed to evaluate the mediating role of satisfaction with job resources in the relationship between servant leadership and life satisfaction. Methods: The study was cross-sectional and explanatory. 620 teachers aged between 20 and 62 years (M = 35 and SD = 9.49) participated in the study. Satisfaction with life, servant leadership, and satisfaction with job resources questionnaires was used in an SEM model. Results: The results indicated that the model obtained an adequate fit, χ2 = 2658, df = 551, p < .001, CFI = 0.941, TLI= 0.936, RMSEA = 0.079, SRMR = 0.070. The results confirm the positive influence of leadership on satisfaction with resources and life satisfaction. Additionally, a positive influence of satisfaction with job resources on life satisfaction was observed. Moreover, the mediation of job resources in servant leadership and life satisfaction was confirmed. Conclusion: Servant leadership, supported by satisfaction with job resources, can reduce effort and associated costs, stimulate personal growth and learning, and improve the well-being of teachers.